Effect of bacterial infection on hepcidin level and its gene polymorphism in β-thalassemia major patient in Erbil province/Kurdistan - Majeed, Dloven Jalal (Journal of Sulaimani Medical College, 2026)
Abstract Background: β-thalassemia major, a genetic disorder causing chronic anemia and iron overload, often leads to dysregulated hepcidin levels, a key iron regulator. Bacterial infections, common in these patients, may alter hepcidin expression. Object: This study aims to assess the impact of bacterial infections on serum hepcidin levels and related HAMP (rs10421768 C-582A > G) in patients with β-thalassemia major. Method: This was cross-sectional study with prospective data collection. Data were collected prospectively from August to December 2024 but analyzed cross sectionally to assess association between bacterial infection, hepcidin levels, and HAMP gene polymorphism. This study involved all patients with β-thalassemia major admitted to the Erbil Thalassemia Center and received blood. Hepcidin levels were determined using a sandwich ELISA (enzyme-linked immunosorbent assay). Bacteria identification was performed by analyzing urine sample using manually and the VITEK 2 system. Additionally genetic was conducted using ARMS-PCR. Result: In 100 β-thalassemia major patients, mean hepcidin level were higher in those with bacterial infection (62.15 ± 6.676 ng/mL) that in non-infected patients (54.65 ± 5.286 ng/mL). Gram-negative bacteria (52.55%) were more common, with Escherichia coli being the most prevalent (31.5%). The HAMP gene polymorphism (rs10421768 C-582A > G) was the most frequently observed as the GA genotype, which showed differences in serum hepcidin levels. Conclusion: Hepcidin levels in β-thalassemia major patients are influenced by both bacterial infections especially Gram-negative bacteria and HAMP (rs10421768 C.-582A>G) gene polymorphism, underscoring the combine role of genetic and infection factors in iron regulation.
Keywords: Key words βthalassemia major; Bacterial infection; Hepcidin level; Gene polymorphism